Restoration of Proresolution Pathway with Exogenous Resolvin D1 Prevents Sevoflurane-Induced Cognitive Decline by Attenuating Neuroinflammation in the Hippocampus in Rats with Type 2 Diabetes Mellitus - Sun, Qingmei; Yan, Hongdan; Chen, Falong; Jiang, Fen; Chen, Wenjuan; Li, Dongliang; Guo, Yongmin (Frontiers in Pharmacology, 2021)
Sevoflurane (SEV), a commonly used volatile anesthetic, has been shown to cause cognitive decline in diabetic rats by aggregating neuroinflammation in the hippocampus, but the underlying mechanisms are unknown. Recent evidence suggests that neuroinflammation could be a consequence of failure to resolve inflammation by specialized pro-resolving lipid mediators including resolvin D1 (RvD1). Here we first examined whether type 2 diabetes mellitus (DM) alters RvD1 proresolution pathway. Diabetic Goto–Kakizaki (GK) rats and non-diabetic Wistar rats received control or 2.6% SEV exposure for 4 h. Seven days after exposure, GK control rats, compared with Wistar control rats, had significantly lower RvD1 levels in plasma and CSF and decreased RvD1 receptor FPR2 expression in the hippocampus. SEV increased RvD1 levels in plasma and CSF and FPR2 expression in the hippocampus in Wistar rats but not in GK rats. We next examined whether RvD1 treatment of GK rats can prevent SEV-induced neuroinflammation and cognitive decline. GK rats received control, SEV or SEV and once-daily treatment with exogenous RvD1 (0.2ug/kg, ip) for 7 days. RvD1 administration markedly increased RvD1 levels in plasma and CSF and FPR2 expression in the hippocampus in GK rats received SEV. Compared with GK control rats, GK rats received SEV exhibited shorter freezing times in trace fear conditioning task, which was accompanied by increased microglia activity and pro-inflammatory cytokine expression in the hippocampus. RvD1 administration attenuated SEV-induced increases in microglia activity and pro-inflammatory cytokine expression in the hippocampus, preventing cognitive decline in GK rats. Notably, neither SEV nor RvD1 altered metabolic parameters in GK rats. The results suggest that RvD1 proresolution pathway is impaired in the brain of diabetic GK rats. which may enhance the susceptibility to SEV, contributing to neuroinflammation and cognitive decline. Restoration of RvD1 proresolution pathway in diabetic GK rats with exogenous RvD1 can prevent SEV-induced cognitive decline by attenuating neuroinflammation in the hippocampus.